Profil Peran Orang Tua dan Guru dalam Penyiapan Masa Transisi Anak ke Sekolah Dasar - Lia Dwi Ayu Pagarwati; Lantip Diat Prasojo; Sugito Sugito; Arif Rohman (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2021)
The purpose of this study is to describe the role of teachers (SD and TK) and parents in preparing for the transition period of children to elementary school in Kecamatan Air Sugihan. This research uses descriptive quantitative research with a survei method. Respondents in this study were 7 first grade elementary school teachers, 11 kindergarten teachers, and 89 parents of students. The study results indicate that child development is not optimal and environmental changes are the main problems in the transition period of children so that the roles of teachers (SD and TK) and parents play an essential role in the transition period of children to produce optimal school readiness. This role is in the form of responsibility for children's school readiness, as a motivator for children, as a role model, as a supervisor and as a place to ask children so that all the needs of children's school readiness are met. Tujuan penelitian ini untuk menggambarkan peran guru (SD dan TK) dan orangtua dalam penyiapan masa transisi anak ke sekolah dasar di kecamatan Air Sugihan. Penelitian menggunakan penelitian kuantitatif deskriptif dengan metode survei. Responden dalam penelitian ini 7 orang guru kelas I SD, 11 orang guru TK, dan 89 orangtua siswa. Hasil dari penelitian menunjukkan bahwa perkembangan anak yang belum optimal dan perubahan lingkungan merupakan masalah utama dalam masa transisi anak sehingga peran guru (SD dan TK) dan orangtua sangat berperan penting dalam hal masa transisi anak agar menghasilkan kesiapan bersekolah yang optimal. Peran tersebut berupa tanggung jawab terhadap kesiapan sekolah anak, motivator bagi anak, sebagai panutan, sebagai pengawas dan sebagai tempat bertanya anak sehingga semua kebutuhan dalam kesiapan sekolah anak terpenuhi.